2021
DOI: 10.3390/nu13103602
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Meat with Non-Meat Protein Sources: A Review of the Drivers and Inhibitors in Developed Countries

Abstract: The overconsumption of meat has been charged with contributing to poor health and environmental degradation. Replacing meat with non-meat protein sources is one strategy advocated to reduce meat intake. This narrative review aims to identify the drivers and inhibitors underlying replacing meat with non-meat protein sources in omnivores and flexitarians in developed countries. A systematic search was conducted in Scopus and Web of Science until April 2021. In total, twenty-three studies were included in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…They also found that, in the informed group, the preference and WTP for the plant-based patty labeled as “made with animal-like protein” exceeded those for the hybrid burger (70% beef and 30% mushrooms) and the plant-based burger “made with pea protein”. As reported by several studies, low prices of non-meat protein sources may act as a driver to accept such products [ 66 ]; however, it will probably take some years to reach price parity with traditional meat [ 4 ].…”
Section: Consumer Behavior Of Plant-based Meat Alternativesmentioning
confidence: 99%
“…They also found that, in the informed group, the preference and WTP for the plant-based patty labeled as “made with animal-like protein” exceeded those for the hybrid burger (70% beef and 30% mushrooms) and the plant-based burger “made with pea protein”. As reported by several studies, low prices of non-meat protein sources may act as a driver to accept such products [ 66 ]; however, it will probably take some years to reach price parity with traditional meat [ 4 ].…”
Section: Consumer Behavior Of Plant-based Meat Alternativesmentioning
confidence: 99%
“…Interestingly, for the MeatPref and BothPos segments, the most frequently given reason for regularly eating meat alternatives was "I like trying new foods". Although food neophobia (i.e., reluctance to try new foods) has been frequently identified as one of the barriers to the consumption of alternative proteins [23,46,66], it may be more important in relation to certain other kinds of meat alternatives, such as insects and cultured meat, than plant-based meat alternatives [23]. Moreover, in the present study, the consumer segments did not differ significantly (according to Tukey's test) in terms of their Food Neophobia Scale scores.…”
Section: Consumption Of Meat and Meat Alternatives And The Underlying...mentioning
confidence: 99%
“…Generally, manufacturers of these products seem to have focused on the known barriers associated with consumer acceptance to market their products. Low levels of acceptance for alternative protein products have been associated with lower perceived product quality (e.g., more artificial and less natural) and perceived health concerns (particularly regarding lack of protein) compared with conventional meat ( 22 , 23 , 43 45 ). About a quarter (26%) of products included in this analysis highlighted the absence of artificial colors, flavors and/or preservatives, and nearly two-thirds (62%) contained at least one protein-related claim.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of this study is the clear definition of alternative protein products and their subcategories, which was easy to operationalise. However, there is no standardized definition of meat and non-meat protein replacements ( 43 ), therefore the categorisation used herein may not be comparable to other studies. This study included more traditional products such as falafel, and processed legume products which other studies have excluded from their analyses.…”
Section: Discussionmentioning
confidence: 99%